Organogenesis formation Porang plant (Amorphophallusmuelleri B.) At Several Concentrations of TDZ (Thidiazuron) - Didik Pudji Restanto; Saputro Gumelar, Bachtiar; Handoyo, Tri; Ubaidillah, Mohammad; Candra Prayoga, Mohammad (Politeknik Negeri Lampung., 2024)
The porang plant (Amorphophallus muelleri B.) is a tuber plant. Porang plant propagation still uses conventional methods by using seeds or frogs that experience dormancy and take a long time to make seeds. The tissue culture technology approach through organogenesis is a solution for the supply of large-scale porang seed material. The research aims to determine the effect of TDZ (Thidiazuron) on the formation of organogenesis. This study used porang leaf explants grown on MS media. The research design used a completely randomized design with one factor, namely TDZ hormone at concentrations of 0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L, and 4 mg/L. The results showed that leaf explants on the addition of TDZ hormone could form organogenesis indirectly, but gave a response to form shoots multiplication. TDZ concentration of 2 mg/L gave the highest proportion value in the parameter of callus formation power of 95%, regeneration power of 88%, and number of shoots of 10.2 shoots.